Respuesta :

Answer:

a)  [tex]\frac{1}{3} m n[/tex]

Step-by-step explanation:

Explanation:-

Given expression

            =    [tex](\frac{(m^5 n^5)^{\frac{1}{6} } }{3 (mn)^{\frac{-1}{6} } } )[/tex]

 we will apply formula

(ab)ⁿ = aⁿ b ⁿ

        =      [tex](\frac{(m^5 n^5)^{\frac{1}{6} } }{3(m)^{\frac{-1}{6} } (n)^{\frac{-1}{6} } } )[/tex]

       = [tex]\frac{1}{3} m^{\frac{5}{6} } n^{\frac{5}{6} } m^{\frac{1}{6} } n^{\frac{1}{6} }[/tex]

base terms are equal then powers will be add

      = [tex]\frac{1}{3} m^{\frac{5+1}{6} } n^{\frac{5+1}{6} }[/tex]

     =  [tex]\frac{1}{3} m^{1} n^{\frac{1}[/tex]

    = [tex]\frac{1}{3} m n[/tex]

ACCESS MORE